2010
DOI: 10.1590/s1516-35982010001200009
|View full text |Cite
|
Sign up to set email alerts
|

Persistence in milk, fat and protein production of primiparous Holstein cows by random regression models

Abstract: -Total numbers of 56,508, 35,091 and 8,326 records of milk, fat, and protein test-day yields, respectively, were used to estimate genetic parameters for six persistency measures on milk, fat and protein productions of Holstein cows reared in Minas Gerais state. Covariance components for additive genetic effects and permanent environmental effects were estimated by REML in random regression models using Legendre polynomials from the third to the sixth order. Overall, models with the highest orders of Legendre p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 16 publications
2
15
2
5
Order By: Relevance
“…Heritability estimates for partial, total 305 days milk yield and different persistency measures are given in Table 4. Part2 and Part3 have the highest (0.307 ± 0.015) and lowest (0.232 ± 0.014) heritabilities for partial milk yield, respectively, and the heritability estimates for 305 days milk yield was 0.305 ± 0.005, which is similar to those obtained by Khorshidie et al, (2012), Cobuci et al, (2005) and Biassus et al, (2010). The level of milk yield has an important influence on persistency.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Heritability estimates for partial, total 305 days milk yield and different persistency measures are given in Table 4. Part2 and Part3 have the highest (0.307 ± 0.015) and lowest (0.232 ± 0.014) heritabilities for partial milk yield, respectively, and the heritability estimates for 305 days milk yield was 0.305 ± 0.005, which is similar to those obtained by Khorshidie et al, (2012), Cobuci et al, (2005) and Biassus et al, (2010). The level of milk yield has an important influence on persistency.…”
Section: Resultssupporting
confidence: 84%
“…Jakobsen et al, (2002) obtained values from 0.09 to 0.24 for persistency of milk yield while Cole and VanRaden (2006) reported heritabilities ranging from 0.10 to 0.11 for persistency of milk yield. Different heritabilities of persistency can be attributed to differences in the definition of the trait and differences in statistical methods used in the calculation of persistency (Biassus et al, 2010;Jakobsen et al, 2002). According to Jakobsen et al, (2002) a good persistency measure should have a high heritability and must be uncorrelated with 305 days milk yield because there is an antagonistic relationship between persistency and 305 days yield.…”
Section: Journal Of Agricultural Studiesmentioning
confidence: 99%
“…For the persistency of F % and P %, h 2 estimates were low. Given that h 2 of persistency varied significantly depending on definition (Biassus et al, 2010), it could be stated that persistency's definition was not optimal for this trait as it was for MY and for P %. However, the SE obtained in this study showed that these estimates of h 2 differ from zero.…”
Section: Resultsmentioning
confidence: 99%
“…Costa et al (2008), Biassus et al (2011), and Cobuci et al (2011) studied the use of random regression models with Legendre polynomials, in order to determine the best order for genetic evaluation of Holstein cattle in Brazil, and to substitute the current 305-day lactation model. However, there are few studies on milk and its components, as fat and protein, in tropical countries as Brazil, using random regression models in the genetic evaluations of Holstein breed (Costa et al, 2008;Biassus et al, 2010). In general, the random regression models using Legendre polynomials of fourth, fifth and sixth orders have been indicated as a good option for conducting genetic evaluations of Holstein cattle; however, there are no comparisons between random regression and lactation models as for the advantages in the gain of reliability of breeding values from studies on Brazilian Holsteins (Costa et al, 2008;Biassus et al, 2010Biassus et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%